The Bequest Transferred Prior to Death: Between Conflict Prevention and Gender-Biased Family Asset Division - Meriyati Meriyati; JM. Muslimin; Nur Hidayah; Ahmad Rodoni (De Jure: Jurnal Hukum dan Syari'ah, 2026)
Gender inequity in bequest practices within the Komering adat community reflects structural inequalities shaped by social, cultural, and ideological factors. Bequest is commonly practiced as a preventive mechanism to avoid inheritance disputes within families. However, this practice tends to privilege men by allocating productive assets, such as land and plantations, primarily to male heirs, while women often receive smaller shares or are positioned as secondary beneficiaries. From a social construction perspective, this pattern reflects patriarchal traditions embedded in customary practices. This study employs a qualitative approach with a socio-juridical research design to examine how social construction and patriarchal values influence bequest practices as an economic instrument within Komering families. Primary data were collected through field observations and in-depth interviews with customary leaders, family members, and women involved in bequest practices. Secondary data were obtained from legal documents, regulations, and academic literature. The analysis draws on patriarchal theory, social construction theory, and Sylvia Walby’s framework to explore the relationship between power structures and cultural legitimacy. The findings reveal that men are consistently prioritised in receiving productive assets, while women generally receive smaller portions of family wealth. This pattern is socially legitimised through norms positioning men as primary family providers. Consequently, women experience reduced access to economic resources, increased financial dependency, and weaker bargaining positions within the social structure. From the perspective of maqāṣid al-syarī‘ah, particularly regarding asset protection and distributive justice, current bequest practices have not fully reflected principles of justice. The gap between legal ideals and social realities indicates the need for reconstructing religious understanding and encouraging social transformation. Strengthening gender-responsive policies and promoting substantive justice-based interpretations of Islamic law are therefore necessary to restore bequest practices as inclusive mechanisms that support welfare and social equity.